2021
DOI: 10.1186/s12947-021-00267-w
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of worsening TR severity after right ventricular lead placement: any added value by post-procedural fluoroscopy versus three –dimensional echocardiography?

Abstract: Background The effect of right ventricular (RV) leads on tricuspid valve has been already raised concerns, especially in terms of prognostic implication. For such assessment, three-dimensional transthoracic echocardiography (3D-TTE) has been used previously but there was no data on the use of post-procedural fluoroscopy in the literature. Methods We prospectively enrolled 59 patients who underwent clinically indicated placement of pacemaker or impl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 13 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…The general progression of TR by one grade in our study was 34.6% and by two or more grades, 15.8%, which is consistent to previous studies [ 3 , 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The progression of TR in group 1 was an effect of TR progression by one grade (43.3% vs. 21.9%, p = 0.033), which was mostly gained by the change from none/trace to mild (31.7%) ( Table 4 ).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The general progression of TR by one grade in our study was 34.6% and by two or more grades, 15.8%, which is consistent to previous studies [ 3 , 4 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. The progression of TR in group 1 was an effect of TR progression by one grade (43.3% vs. 21.9%, p = 0.033), which was mostly gained by the change from none/trace to mild (31.7%) ( Table 4 ).…”
Section: Discussionsupporting
confidence: 93%
“…Notwithstanding, in this study, there was no difference in TR occurrence between the groups, which is consistent with other authors [ 7 , 8 , 9 , 10 , 11 , 21 , 30 ]. Yu et al observed that when the pacing lead is located in the RV apex, it is more likely to affect the posterior leaflet [ 36 ], and some authors suggest that the septal and posterior leaflets are the most affected by the leads, despite the pacing lead localization [ 7 , 14 , 15 , 23 , 24 , 29 , 31 , 34 ]. However, contrary to this, Cheng et al [ 31 ] found that a significant increase in the PISA radius of TR after implantation of CIED was observed more often in the group with lead tips in the IVS.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations